Evolution of the Judicial Opinion : Institutional and Individual Styles. - Popkin, William D. (NYU Press, 2007)
In this sweeping study of the judicial opinion, William D. Popkin examines how judges' opinions have been presented from the early American Republic to the present. Throughout history, he maintains, judges have presented their opinions within political contexts that involve projecting judicial authority to the external public, yet within a professional legal culture that requires opinions to develop judicial law through particular institutional and individual judicial styles. Tracing the history of judicial opinion from its roots in English common law, Popkin documents a general shift from uno.